Crystal structures of Mycobacterium tuberculosis and Mycobacterium thermoresistibile glycyl-tRNA synthetases in various liganded states - Michael K. Fenwick; Amy E. DeRocher; Justin K. Craig; Elizabeth K. Harmon; Steve Seibold; Lijun Liu; Kevin P. Battaile; Lynn K. Barrett; Wesley C. Van Voorhis; Isabelle Q. Phan; Bart L. Staker; Sandhya Subramanian; et al. (PLoS ONE, 2025)
Glycyl tRNA synthetases (GlyRSs) are prospective drug targets for combating Mycobacterium tuberculosis (Mtb) and cancer in humans. These synthetases are of the α2-subtype, with the ortholog in humans being dual targeted to the cytosol and mitochondria. Whereas the human enzyme has been structurally characterized previously in several liganded states, no structures of MtbGlyRS have thus far been reported. Here, we describe our recent work with MtbGlyRS and the closely-related Mycobacterium thermoresitibile GlyRS (MtrGlyRS), which progressed through all phases of the structural genomics pipeline, for the purpose of facilitating structure-based drug discovery. MtbGlyRS was expressed in Mycobacterium smegmatis and MtrGlyRS in Escherichia coli. Crystal structures are described for complexes of the two enzymes with adenosine monophosphate (AMP) and glycyl-sulfamoyl-adenylate (glycyl-AMS) at resolutions of 1.65/2.90 and 2.25/1.95 Å, respectively, and for MtrGlyRS in its apo state at 2.85 Å. Despite crystallizing in the dimeric state characteristic of many class II synthetases, the two enzymes elute predominantly as monomers during size exclusion chromatography. Strikingly, significant portions of the dimer interface and active site are unstructured in the MtrGlyRS apoenzyme crystal. AMP orders two tRNA recognition loops and a section of the insertion domain, and glycyl-AMS further stabilizes the structure, including the closure of a lid motif. Both the active and anticodon binding sites display structural differences with the human GlyRS and thus the collection of crystal structures should be useful for guiding drug development efforts targeting the various characterized structural states.